Incidence and patterns of ALK FISH abnormalities seen in a large unselected series of lung carcinomas - Dai, Zunyan (BioMed Central, 2012)
BACKGROUND: Anaplastic lymphoma receptor tyrosine kinase (ALK) gene rearrangements have been reported in 2-13% of patients with non-small cell lung cancer (NSCLC). Patients with ALK rearrangements do not respond to EGFR-specific tyrosine kinase inhibitors (TKIs); however, they do benefit from small molecule inhibitors targeting ALK. RESULTS: In this study, fluorescence in situ hybridization (FISH) using a break-apart probe for the ALK gene was performed on formalin fixed paraffin-embedded tissue to determine the incidence of ALK rearrangements and hybridization patterns in a large unselected cohort of 1387 patients with a referred diagnosis of non-small cell lung cancer (1011 of these patients had a histologic diagnosis of adenocarcinoma). The abnormal FISH signal patterns varied from a single split signal to complex patterns. Among 49 abnormal samples (49/1387, 3.5%), 32 had 1 to 3 split signals. Fifteen samples had deletions of the green 5(′) end of the ALK signal, and 1 of these 15 samples showed amplification of the orange 3(′) end of the ALK signal. Two patients showed a deletion of the 3(′)ALK signal. Thirty eight of these 49 samples (38/1011, 3.7%) were among the 1011 patients with confirmed adenocarcinoma. Five of 8 patients with ALK rearrangements detected by FISH were confirmed to have EML4-ALK fusions by multiplex RT-PCR. Among the 45 ALK-rearranged samples tested, only 1 EGFR mutation (T790M) was detected. Two KRAS mutations were detected among 24 ALK-rearranged samples tested. CONCLUSIONS: In a large unselected series, the frequency of ALK gene rearrangement detected by FISH was approximately 3.5% of lung carcinoma, and 3.7% of patients with lung adenocarcinoma, with variant signal patterns frequently detected. Rare cases with coexisting KRAS and EGFR mutations were seen.